Pengaruh Variasi Bentuk Plat Terhadap Performansi Solar Water Heater - Darwin Harun; Muhammad Ilham Maulana; Teuku Syahrul; Masri Ibrahim (Jurnal Teknik Mesin Unsyiah, 2020)
Thermal energy is one form of energy that is very crucial for human being. It can be obtained through the sun, i.e, that is solar energy. Solar energy is used widely both in industry and houshold. One of the most important component of solar water heater is thermal energy collector or known as absorber. Solar collector is a device utilized to convert sun radiation to thermal energy. This research wanted to examine the effect of different shapes of collector. The methodolody used is by varying the shapes of plat plate, where plate A has a square shape and plate B has has isosceles shape. Collector dimension is 1.5x0.8 m with these two shapes constructed from stainless steel. Pipe used for fluid is made from copper with 1 in diameter and 1.4 m length. Thermal insolation is used from rubber to decrease heat loss from pipe. Plate B collector with isosceles shape showed the highest efficiency compared to plate A collector with square shape. The highest outlet fluid temperature from plate B is 670C with sun radiation 1198 W/m2. The highest useful energy is 209.91 Watt from plate B at 13.30 and efficiency is 16.23% at 13.00WIB.